Bell’s Palsy Following Pfizer–BioNTech COVID-19 Vaccination - Hamzah, Mohd Hafiz; Ramli, Ramiza Ramza (International Journal of Human and Health Sciences (IJHHS), 2022)
COVID-19 is the latest pandemic announced by the World Health Organization (WHO) in March 2020. Immunity can be achieved by preventive immunisation of the population. Pfizer–BioNTech COVID- 19 vaccine is the first vaccine produced and safely used for the public with an efficacy rate of 95% in the prevention of COVID-19. Despite the excellent efficacy, adverse effects of the vaccine, although rare, should be monitored. Bell’s palsy following COVID-19 vaccination is a very rare adverse effect reported. A healthy 38-year-old Malay lady came to the emergency department Hospital Universiti Sains Malaysia (HUSM) complaining of sudden onset left-sided facial asymmetry three hours after she received the second dose of Pfizer–BioNTech COVID-19 vaccine. Facial examination showed left facial nerve palsy (House Brackmann grade 2). She was treated for left Bell’s palsy post COVID-19 vaccination; she was prescribed oral prednisolone and referred to a physiotherapist for facial exercise. After two weeks, Bell's palsy was completely resolved. Bell’s palsy following COVID-19 vaccination is a very rare adverse effect reported. Despite this rarity, the incidents of Bell’s palsy were cited as medically attended adverse events (MAAE) during the Pfizer– BioNTech COVID-19 vaccine clinical trial. In our case, the timing and onset of the patient's symptoms and signs suggested that it was an adverse effect related to the vaccination. Currently, the mechanism of COVID-19 vaccines causing facial nerve palsy is unclear and warrants further investigation. Bell’s palsy associated with COVID-19 vaccination is a very rare adverse effect, which fortunately can be treated with oral steroids. Despite that, the benefits of COVID-19 vaccination outweigh the risks, in the quest to curb this devastating pandemic. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S42